Hepatoprotective effect of fetal tissue cytosol and its thermostable fraction in rats with carbon tetrachloride-induced hepatitis - Cherkashina, DV; Petrenko, AYu (Bull Exp Biol Med. 2006 Apr;141(4):544-547, 2006)
Pretreatment of rats with cytosol of fetal tissue or its thermostable fraction prevented death of animals from CCl4 intoxication, decreased serum transaminase activities and level of TBA-reactive products, and normalized the prooxidant/antioxidant balance in the liver. The effect of cytosol was more pronounced than that of its thermostable fraction.
Cherkashina DV, Petrenko AY. Hepatoprotective effect of fetal tissue cytosol and its thermostable fraction in rats with carbon tetrachloride-induced hepatitis. Bull Exp Biol Med. 2006 Apr;141(4):544-547
Keywords: CCl4-induced hepatitis; liver injury; fetal tissue cytosol; bioregulators; prooxidant/antioxidant balance